The Sage Handbook of Asian Foreign Policy - Inoguchi, Takashi (London : SAGE Publications Ltd, 2020)
Comprising 60.3 percent of the world's 7.2 billion population, Asia is an enigma to many in the West. Hugely dynamic in its demographic, economic, technological and financial development, its changes are as rapid as they are diverse. The SAGE Handbook of Asian Foreign Policy provides the reader with a clear, balanced and comprehensive overview on Asia's foreign policy and accompanying theoretical trends. Placing the diverse and dynamic substance of Asia's international relations first, and bringing together an authoritative assembly of contributors from across the world, this is a reliable introduction to non-Western intellectual traditions in Asia. VOLUME 1: PART 1: Theories; PART 2: Themes; PART 3: Transnational Politics; PART 4: Domestic Politics; PART 5; Transnational Economics. VOLUME 2: PART 6: Foreign Policies of Asian States; Part 6a: East Asia; Part 6b: Southeast Asia; Part 6c: South & Central Asia; Part 7: Offshore Actors; Part 8: Bilateral Issues; Part 9: Comparison of Asian Sub-Regions.
Description based on XML content.
Keywords: International Relations of Asia Pacific; Asian Politics; Comparative Foreign Policy